2000
DOI: 10.1021/ja992989z
|View full text |Cite
|
Sign up to set email alerts
|

Mn2+ Sites in the Hammerhead Ribozyme Investigated by EPR and Continuous-Wave Q-band ENDOR Spectroscopies

Abstract: Metal ions are critical to the structure and function of many RNA molecules, but measuring detailed coordination environments in RNA is challenging under solution conditions. The phosphodiester bond cleavage reaction of the hammerhead ribozyme is activated by Mn 2+ , which provides a paramagnetic probe for EPRbased spectroscopic techniques. In this study, EPR and continuous-wave Q-band (34 GHz) electron nuclear double-resonance (ENDOR) spectroscopies have been used to investigate the coordination environment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
55
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 58 publications
8
55
1
Order By: Relevance
“…1A) is slightly greater than the others immediately downfield. This may be compared with the identical feature seen for Mn(II) bound to the hammerhead ribozyme as contrasted with free Mn(H 2 O) 6 2ϩ , the latter complex showing a more equitable distribution of intensities across this high field hyperfine triplet (26,27). This observation supports protein-bound rather than freely solvated manganous ions as the source of the EPR signals reported herein.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…1A) is slightly greater than the others immediately downfield. This may be compared with the identical feature seen for Mn(II) bound to the hammerhead ribozyme as contrasted with free Mn(H 2 O) 6 2ϩ , the latter complex showing a more equitable distribution of intensities across this high field hyperfine triplet (26,27). This observation supports protein-bound rather than freely solvated manganous ions as the source of the EPR signals reported herein.…”
Section: Resultsmentioning
confidence: 78%
“…environment from forbidden {⌬M S ϭ Ϯ1, ⌬M I ϭ Ϯ1} transitions that gain intensity through the small axial zero-field splitting coupling to the hyperfine transition intensity in second and third order perturbation theory (25,26). Notably, the intensity of the higher-field hyperfine line (sharp peak just below 3600 G in the spectrum of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison with protein-metal binding sites, far less is known about the bonding properties and homogeneity of the metal sites in RNA. Yet as a paramagnetic substitute, Mn(II) allows detailed investigations of these properties in RNA by EPR methods [35].…”
Section: Mn-containing Biological Systemsmentioning
confidence: 99%
“…Biochemical and EPR spectroscopic studies carried out by DeRose and coworkers [92,94] found that only one of these sites tightly binds its respective metal ion (k d ≤ 10 µM), and that this site must be populated for "catalytic" activity. However, all available spectroscopic evidence indirectly suggested that the high-affinity binding site exists between the N7 of a guanine residue (G10.1) and the phosphate oxygen of an adjacent adenine (A9), about 2.0 nm from the site of RNA cleavage [35,92,[95][96][97][98].Only recently has this tentative assignment been confirmed through ESEEM spectroscopic measurements of site-specific isotope labeling of the G10.1 nitrogens [99]. Herein, we report results from EPR spectroscopic experiments at multiple frequencies to study a set of simple nucleotide and RNA Mn(II) complexes.…”
mentioning
confidence: 99%
“…[37] A further mimic for the diamagnetic Mg 2+ is the paramagnetic Mn 2+ ion. The latter is used for EPR [38,39] and also NMR studies, where the resonances are severely broadened upon binding of Mn 2+ in the vicinity. [26,40,41] Outer sphere binding of Mg 2+ can be probed with [Co(NH 3 ) 6 ] 3+ (see also Section 3).…”
Section: Nmr Strategies To Investigate M N+ Binding To Nucleic Acidsmentioning
confidence: 99%